VD_FINDINFO HC / 2019 / 807 vom 18. Juli 2019 - VD Tribunal cantonal (2019)
PREUVE À FUTUR, REJET DE LA DEMANDE, ACTION EN DÉSAVEU, RESTITUTION DU DÉLAI, JUSTE MOTIF, PROFIL D'ADN | 256c al. 3 CC, 158 al. 1 CPC (CH), 308 al. 1 let. a CPC (CH)